(untitled) (ҚазҰУ Хабаршысы. География сериясы, 2022)
Since the beginning of the 21th century, China has implemented a large-scale ecological restoration policy. Evaluating the performance of this policy after implementation is an important topic. In this paper, transaction cost analysis is introduced into the performance evaluation of ecological restoration projects. The transaction costs are divided into five parts, including costs related to search, contracting, construction and operating, monitoring the cost of default, and seeking compensation. The model used for calculating transaction costs is provided. The concept and composition index of structure and performance indices are analyzed. The calculation model of the structure and performance indices is developed as the weighted sum of three indicators: endogenous transaction costs as a part of transaction costs, the proportion of farmers’ input in production costs, and the proportion of transaction costs in total costs. Chicheng County, Hebei Province, China was studied as an example. The transaction costs of three categories of projects that have been implemented were calculated, including Returning Farmland to Forest, Small Watershed Management, and Grazing Prohibition, and the average performance of the projects and the change of performance during project execution were analyzed. Transaction cost and performance calculation will provide a new perspective for the comparison and performance evaluation of different ecological restoration projects, which is of great significance.